Relaciones entre el empleo, calidad de vida y gran empresa en la producción para exportación de espárragos en el Perú: El caso de los valles de La Libertad e Ica - López Mas, Johans Julio E. V. (2009)
The purpose is to note the economic and population dynamics from the comparison between asparagus production and exports in two valleys of peruvian coast: Ica in southern Peru and Viru and northern Peru. This is an example of how peruvian coast is incorporated into the logic and dynamic of the global fresh food system and it assumes with asparagus a leadership position in the international market. Technological and producivity levels in the two valleys mentioned are different (in many factors, such as in productivity per hectare) as well as distances to collection and export centers; nevertheless, we perceive the leadership corporate tendency in complex agroindustrial modern corporates, combining the creation of R&D-based advantages, diversificating crops, targeting markets, and maintaining cheap labor cost exploitation.